Achievements of the Summits of the Americas : from Mar del Plata to Port of Spain (OAS WashingtonUS, 2009)
Focuses on work done by 12 institutional partners of the Joint Summit Working Group since the Fourth Summit of the Americas in the areas of growth with employment, training the labour force, micro-, small- and medium-sized enterprises, creating decent work, strengthening democratic governance, and social development. Provides a brief overview of strategies and actions that can contribute to the implementation of the commitments being made in the framework of the Fifth Summit of the Americas in Port of Spain, Trinidad and Tobago in April 2009.
Keywords: ECONOMIC AND SOCIAL DEVELOPMENT